Training on Development of Work Relationships and Social Media Marketing in MSMEs - Bramma Aji putra; Muinah Fadhilah; Ambar Lukitaningsih; Gendro Wiyono (Faculty of Economics Universitas Sarjanawiyata Tamansiswa, 2022)
This service aims to provide of training to handicraft SMEs in Yogyakarta. The COVID-19 pandemic has had a negative impact on MSMEs, one of which is handicraft MSMEs. The purpose of this training is a strengthening the development of work relations and product marketing through social media. The results obtained after the training show that strengthening work relations and using social media is effective as a marketing medium and increasing turnover. In addition, the development of social media also needs to involve the youth for increasing digital marketing innovation.